2023
DOI: 10.3390/biology12071008
|View full text |Cite
|
Sign up to set email alerts
|

Proline Isomerization: From the Chemistry and Biology to Therapeutic Opportunities

Deepti Gurung,
Jacob A Danielson,
Afsara Tasnim
et al.

Abstract: Proline isomerization, the process of interconversion between the cis- and trans-forms of proline, is an important and unique post-translational modification that can affect protein folding and conformations, and ultimately regulate protein functions and biological pathways. Although impactful, the importance and prevalence of proline isomerization as a regulation mechanism in biological systems have not been fully understood or recognized. Aiming to fill gaps and bring new awareness, we attempt to provide a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 310 publications
0
5
0
Order By: Relevance
“…As noted earlier, crystallins are regulated developmentally, , and the CLD and the PPIase activity of CY of Ranbp2 modulate protein homeostasis in vitro and physiologically (Figure a). ,,, The PPIase activity is used as an in vitro proxy assay to estimate varied roles of catalysis of cis–trans isomerization of a linker proline in proteostasis, protein biogenesis, and signal transduction . As shown by our prior works and other independent studies of orthologous CY of bovine and human Ranbp2 (Figure a), CY has PPIase activity with the de facto isomer-specific proteolysis-coupled assay (ISP) for measuring proline isomerase of modified substrates with the general formula, succinyl (Suc)-Ala-Xaa- cis -Pro-Phe- p -nitroanilide (pNA). ,,, In this assay, the p -nitroanilide amide bond is hydrolyzed by α-chymotrypsin only when the Xaa-Pro bond of the chromogenic tetrapeptide is in the trans conformation .…”
Section: Resultsmentioning
confidence: 83%
“…As noted earlier, crystallins are regulated developmentally, , and the CLD and the PPIase activity of CY of Ranbp2 modulate protein homeostasis in vitro and physiologically (Figure a). ,,, The PPIase activity is used as an in vitro proxy assay to estimate varied roles of catalysis of cis–trans isomerization of a linker proline in proteostasis, protein biogenesis, and signal transduction . As shown by our prior works and other independent studies of orthologous CY of bovine and human Ranbp2 (Figure a), CY has PPIase activity with the de facto isomer-specific proteolysis-coupled assay (ISP) for measuring proline isomerase of modified substrates with the general formula, succinyl (Suc)-Ala-Xaa- cis -Pro-Phe- p -nitroanilide (pNA). ,,, In this assay, the p -nitroanilide amide bond is hydrolyzed by α-chymotrypsin only when the Xaa-Pro bond of the chromogenic tetrapeptide is in the trans conformation .…”
Section: Resultsmentioning
confidence: 83%
“…While the finding that FASN regulates p65 stability by impacting the phosphorylation status of the p65 Thr 254 residue, thereby, affecting the isomerization of p65 by Pin1 ( Fig. 8 ) is intriguing, it is not surprising since Pin1 is known to regulate stability of many proteins by binding to and isomerizing these proteins upon phosphorylation at the consensus Ser/Thr-Pro motif ( 43 ) including Thr 254 -phosphorylated p65 ( 36 ). It has been reported that activated p65 in the nucleus is not bound by the inhibitory subunit IκBα, leaving Thr 254 exposed and allowing its phosphorylation ( 36 ) followed by recruitment of and isomerization by Pin1.…”
Section: Discussionmentioning
confidence: 99%
“…Although Pin1 binding to and isomerizing phosphorylated substrate proteins, such as p65 and p53 ( 36 , 43 ) results in the stabilization of these proteins, the molecular mechanism of the protein stabilization following isomerization is unknown. However, it was thought that phosphorylation and isomerization of these proteins facilitate their translocation into nucleus where they exert their functions as transcription factors, which may prevent them from binding by E3 ubiquitin ligase and degradation by proteasomes in the cytoplasm ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Proline’s cyclic structure facilitates cis–trans interconversion, governing protein conformation and function . In the trans configuration, proline has ω = 180°, while in cis , ω = 0°.…”
Section: Discussionmentioning
confidence: 99%
“…Proline's cyclic structure facilitates cis−trans interconversion, governing protein conformation and function. 77 In the trans configuration, proline has ω = 180°, while in cis, ω = 0°. A transition of cis to a syn (ω = 90°) state needs to overcome a ∼30 kcal mol −1 energy barrier, leading to a predominantly trans conformation.…”
Section: Negative Regulatory Phosphorylation Site In Her2mentioning
confidence: 99%